INFORMATION TECHNOLOGY OF RATIONAL RESOURCE ALLOCATION IN THE SYSTEM OF BUSINESS PROCESSES OF THE ORGANIZATION - Vasily Vartanian; Yurii Romanenkov; Yurii Pronchakov; Tieimur Zieiniiev (Сучасний стан наукових досліджень та технологій в промисловості)
The problem of rational distribution of investment resources among individual business processes of the organizational and technical system is considered taking into account the real characteristics of the primary data (in particular, the interval uncertainty of expert assessment). The subject matter of the study is the models and methods of information technology of rational distribution of resources in the system of business processes of the organization, the goal is to ensure the quality of organization management by creating applied information technology of rational resource distribution in the system of business processes taking into account the interval of expert assessments. The following tasks were solved in the work: the matrix method for assessing the level of efficiency of the hierarchical system of business processes of the organization was developed; methods and means of infographic analysis of aggregated indices of multidimensional objects and systems were developed; an optimization model of resource distribution in the system of business processes of the organization was developed; the applied information technology of rational distribution of resources in the system of business processes of the organization was created. The following methods were used as the basis of the research methodology: the matrix analysis was used for developing the matrix method for assessing the level of efficiency of the hierarchical system of the organization business processes as well as for developing methods and tools for the infographic analysis of aggregated indices of multidimensional objects and systems; the methods of linear programming and interval analysis were used for developing an optimization model of resource distribution in the system of business processes of the organization; the principles of system analysis were used for developing applied information technology, rational allocation of resources in the system of business processes of the organization. As a result, the methodical support of information technology for the rational distribution of resources in the system of business processes of the organization was developed. The place of the described models is shown in the process of supporting decisions on distributing resources in the system of business processes of the organization taking into account the interval of expert assessments.